Echoing colonnades transforming the vision theater corner into a post-production and motion capture studio through adaptive reuse to revitalize Cebuano language - Bagnes, Angela S.; Richelle Rhea R. Baria (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
The essence, structure, and beauty of language and architecture have always been rooted into how these art forms embed and celebrate our values and culture as society. There exists a relationship that can enable a more tangible expression of our ideals, and more so contribute to their concrete preservations. This is the inception of design and narrative that shall be defined in this design project. This study focuses on the adaptive reuse of a corner lot at the entry point of Colon Street, Cebu City, transforming it into a mixed-use commercial and studio facility that promotes Cebuano language and cultural appreciation. The design aims to predict user behavior through multiple theories in architectural cognition from various fields including language, emotional geography, neuroarchitecture, film, and synesthesia, contributing to the local creative economy and preserving Cebu’s historic district by revitalizing it with a modern purpose. The project seeks to identify how architecture can evoke language and cultural appreciation, determine the relevance of the site to its users, and explore an architectural style inherently Cebuano. The broader significance lies in addressing the Philippine dilemma of diminishing mother tongue languages while contributing to Cebu's creative economy in film, music, and animation. Methodologically, the study employed narrative and thematic analysis of interviews and consultations with Cebuano citizens, site users, and local government officials, framed using Schwarts’s (1994) motivational values. Insights were enriched by analyzing excerpts from Cebuano literature and official historical references. Site analysis, conducted from October 6 to 8, 2024, involved reviewing as-built plans and architectural precedents. The design outcome emphasizes multi-sensory design principles to engage users, anchored by studies and theories from Kaplan’s Preference Model, Assem, Khodeir and Fathy’s Summary of Neuro-architectural Design Elements
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Buildings -- Remodeling for other use -- Cebu City